Game-theoretic approach to understanding status transition dynamics and employee performance enhancement in organizations - Wu, Mengyun; Zhu, Yuqing; Yang, Ting; Xu, Yifan (Frontiers in Physics, 2023)
To foster high-quality economic development, it is critical to not only enhance the 'hard environment', such as infrastructure, but also to make significant strides in the 'soft environment', such as the relationship between government and businesses. This study posits that the government, industry associations, and enterprises should collectively participate in fostering a 'cordial and clean' government-business relationship. By resolving the equilibrium solution of the three-party game, it has been identified that achieving the goal of constructing a cordial and clean government-business relationship and aligning with the ambitions of enterprises necessitates policy guidance and a balance of interests among the government, industry associations, and enterprises. The research also contributes to the beneficial exploration of game theory, by constructing a network model from the perspective of public management and integrating it with the practice of local administrative reform. This integration is particularly relevant for industry associations, and their systematic analysis further enhances the practical applicability of the research.